2000
DOI: 10.1046/j.1365-2508.2000.00373.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal balloon endometrial destruction: the outcome of treatment of 117 women followed up for a maximum period of 4 years

Abstract: Objective To study the long‐term results of treatment for menorrhagia involving the thermal destruction of the endometrium by means of a balloon catheter. Design Between August 1993 and December 1996, 117 women were treated and, in a prospective study, 116 (99%) of them were followed up with consultations and questionnaires. No pretreatment with gonadotrophin‐releasing hormone (GnRH) analogues was given. Setting Gynaecology department at a university hospital. Results There were no immediate peroperative compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 11 publications
3
13
3
Order By: Relevance
“…Results of the present study compare favourably with those reported after both hysteroscopic first-generation methods for endometrial ablation such as endometrial resection, rollerball and Nd-YAG laser ablation (Magos et al, 1991;Garry et al, 1995;Goldrath, 1995;Valle, 1995;Friberg et al, 1996;O'Connor and Magos, 1996) and second-generation ablation methods such as Thermachoice TM , NovaSure TM and hydrothermal ablation (Amso et al, 1998;Meyer et al, 1998;Friberg and Ahlgren, 2000;Corson, 2001;Hefni et al, 2002;Abbott et al, 2003). Also, the low failure rate observed in the present study was comparable to those reported previously with the use of either first-or secondgeneration techniques of endometrial ablation (Pinion et al, 1994;O'Connor andMagos, 1996, Phillips et al, 1998;Hefni et al, 2002).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Results of the present study compare favourably with those reported after both hysteroscopic first-generation methods for endometrial ablation such as endometrial resection, rollerball and Nd-YAG laser ablation (Magos et al, 1991;Garry et al, 1995;Goldrath, 1995;Valle, 1995;Friberg et al, 1996;O'Connor and Magos, 1996) and second-generation ablation methods such as Thermachoice TM , NovaSure TM and hydrothermal ablation (Amso et al, 1998;Meyer et al, 1998;Friberg and Ahlgren, 2000;Corson, 2001;Hefni et al, 2002;Abbott et al, 2003). Also, the low failure rate observed in the present study was comparable to those reported previously with the use of either first-or secondgeneration techniques of endometrial ablation (Pinion et al, 1994;O'Connor andMagos, 1996, Phillips et al, 1998;Hefni et al, 2002).…”
Section: Discussionsupporting
confidence: 75%
“…First, the diameter of the device's catheter is smaller (6 mm) compared to 9 mm in the older version, thus obviating the need for cervical dilatation in most cases and allowing the procedure to be performed under local anaesthesia (Friberg and Ahlgren, 2000), although this was not preferred by our patients. Secondly, the balloon length is more adjustable to the cavity, thus adapting to a wider variety of cavity configurations.…”
Section: Discussionmentioning
confidence: 98%
“…Compared to other thermal balloon systems such as Thermachoice TM and Easy TM , although results are similar (Amso et al, 1998;Meyer et al, 1998;Friberg and Ahlgren, 2000), the Cavaterm TM differs in three important respects. First, the balloon is made of silicone rather than latex, which renders it highly flexible and more robust.…”
Section: Discussionmentioning
confidence: 82%
“…The Cavaterm can also be used under local anaesthesia (Friberg and Ahlgren, 2000), although this was not preferred by our patients.…”
Section: Discussionmentioning
confidence: 99%
“…A number of the reports emanate from 1 group, with the most recent update describing 106 of the 117 originally treated women 10 to 49 months after treatment. 73,74 The hysterectomy rate during the follow-up period was 8.6% (10/116) with 7 cases associated with submucosal leiomyomas. The amenorrhea rate was 29.4% but 7 of these patients were postmenopausal at the time of follow-up.…”
Section: Cavatermmentioning
confidence: 96%